Test body for testing stain resistance of engineering machinery coating as well as preparation method and testing method of test body
By using a test body composed of hydraulic oil, lubricating oil, etc., combined with artificial accelerated aging and visual evaluation methods, the problem of difficult to detect the stain resistance of engineering machinery coatings in the prior art is solved, and a more accurate and efficient test effect is achieved.
Patent Information
- Application Number
- CN202411923279.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to quickly and accurately detect the stain resistance of the surface coating of construction machinery, and it is impossible to establish the correspondence between laboratory test data and actual use scenarios.
A test substance consisting of hydraulic oil, lubricant, wetting agent, atmospheric test dust standard samples, melanin and solvents is used to simulate the use environment of construction machinery through manual acceleration aging, and the stain resistance of the coating is evaluated in combination with visual staining, loss of light and discoloration.
A stain resistance testing method is provided that is closer to the actual environment of construction machinery, which can quickly and accurately reflect the stain resistance performance of the coating, improve the testing efficiency and reduce the preparation cost.
Smart Images

Figure CN119595395A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a test piece for testing the anti-fouling performance of a coating, in particular to a test piece for testing the anti-fouling performance of a polyurethane coating of an engineering machinery and a preparation method and a testing method thereof. Background Art
[0002] Anti-fouling performance is one of the important indicators that affect the appearance quality of the coating of engineering machinery products, and directly affects the manufacturing cost of engineering machinery factories and the cleaning and maintenance investment of users. The reasons are: first, when the products are stored in the factory, the coating surface is affected by atmospheric dust and air pollutants in the factory, resulting in a decline in product appearance quality and the need for rework; second, after working in a harsh environment, the coating surface is dirty and difficult to clean, and the cleaning investment increases, which also affects the overall appearance of the vehicle and reduces the product's value retention rate.
[0003] For a long time, coatings workers have been seeking the best way and method to solve the stain resistance test of coatings, and there are many related reports. For example, CN 105445235A disclosed on March 30, 2016, a method for rapid detection of stain resistance of latex paint film, "Stain resistance and test of organic fluorine coatings" (Liu Dong et al., "Coatings Industry" 2004 No. 4, pp. 41-43) and "Comparison and thinking of stain resistance test methods for exterior wall coatings" (Ren Shiwei et al., "Coatings Industry" 2015 No. 4, pp. 64-68) disclosed stain resistance test methods for coatings, etc.
[0004] Relevant departments in my country have also issued some relevant standards, such as GB / T 9780-2013 "Test Method for Stain Resistance of Architectural Coatings". GB / T9755-2014 "Synthetic Resin Emulsion Exterior Wall Coatings" and JG / T172-2014 "Elastic Architectural Coatings" also include stain resistance test methods for related coatings.
[0005] However, at present, there is no stain resistance testing method that can quickly identify the differences in stain resistance of product surface coatings, nor can it establish a correspondence between the relevant data obtained from laboratory tests and actual on-site usage scenarios.
[0006] GB / T 9780-2013 "Test Method for Anti-fouling of Architectural Coatings" used in the field of architectural coatings is not applicable to the field of engineering machinery coatings. The main reason is that most of the coatings of engineering machinery are two-component polyurethane or fluorocarbon topcoats, which have high film density, smooth surface and low surface tension. The test pollutants and test methods described in GB / T 9780-2013 cannot effectively judge the difference in anti-fouling performance of the surface coating of engineering machinery to different pollution environments, different pollution sources and different pollutants.
[0007] CN 115420582 A disclosed a specimen for stain resistance test and its preparation method and test method on December 2, 2022. The specimen includes a mixture and water, and the plastic viscosity is greater than 1Pa·s and less than 2Pa·s. The weight ratio of each component of the mixture is: 25-35% washed porcelain clay, 15-25% pyrophyllite, 15-25% washed kaolin, 5-15% sericite, 5-15% potassium feldspar, 3-13% washed ball clay, and 2% dolomite. According to the description, it is only suitable for toilet stain resistance test.
[0008] CN 105628624A disclosed a method for quickly evaluating pollution resistance and a special standard pollutant on June 1, 2016, wherein the special standard pollutant contains 12 chemical elements such as C, O, Na, Mg, Al, Si, S, Cl, K, Ca, Ti, and Fe in a specified proportion. The pollutant standard comprises component A, component B, component C, and component D, wherein component A is composed of acrylic resin, NaCl, KCl, MgO, and TiO2, component B is powder or dust, component C is test dust (or experimental dust), and component D is composed of carbon black, natural loess, CaCO3, and dust. The test method is to analyze the pollutants in the urban atmospheric environment, prepare standard pollutants with similar chemical element composition, use wind to adsorb the pollutants on the test plate, simulate the environment before raining under high humidity conditions, and then wash and heat the test plate, and then evaluate the pollution resistance of the test plate by testing the brightness and reflectivity of the test plate. Its method mainly simulates the contamination of exterior wall paint coatings in the urban atmospheric environment. Its pollutants are significantly different from the oil contamination that engineering machinery is susceptible to in its use environment. Its testing method also only simulates the pollution under high humidity conditions and cannot reflect the complexity of the actual climate environment. Moreover, the preparation of the special standard pollutants described therein is extremely troublesome, and the operating steps of the testing method are also quite complicated.
[0009] Furthermore, in actual applications, the environmental conditions faced by construction machinery coatings are worse than those faced by general architectural coatings. Therefore, construction machinery coatings are affected by a variety of external environmental factors that architectural coatings are not exposed to, such as oil pollution during assembly, storage, and maintenance, sewage, sludge, and high-concentration dust pollution during use, etc. Using the pollutants faced by general architectural coatings to test and evaluate the anti-fouling performance of construction machinery surface coatings in a simple flushing manner has low accuracy. Summary of the invention
[0010] The first technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a test specimen with a simple formula that can be used to more accurately evaluate the anti-fouling performance test of the surface coating of engineering machinery.
[0011] The second technical problem to be solved by the present invention is to provide a method for preparing the specimen.
[0012] The third technical problem to be solved by the present invention is to provide a method for using the test body to more accurately test and evaluate the anti-fouling performance of the surface coating of engineering machinery.
[0013] The technical solution adopted by the present invention to solve the first technical problem is to provide a specimen for testing the anti-fouling performance of the surface coating of engineering machinery, which is mixed with the following raw material components in weight percentage: 10-30% hydraulic oil, 10-30% lubricating oil, 2-5% wetting agent, 20-40% standard sample of atmospheric test dust, 5-15% melanin, and 10-30% solvent.
[0014] Furthermore, the hydraulic oil is L-HM anti-wear hydraulic oil (high pressure) or L-HM anti-wear hydraulic oil (ordinary) in GB11118.1.
[0015] Furthermore, the lubricating oil is GBW13986 PAO lubricating oil density standard material.
[0016] Furthermore, the wetting agent is TEGO 270 or TEGO 4100.
[0017] Furthermore, the standard sample of atmospheric test dust is loess dust (GBW08305) or coal fly ash (GBW08401).
[0018] Furthermore, the melanin is water-soluble melanin (CAS 8005-03-6) or alcohol-soluble melanin (CAS 8005-02-5).
[0019] Furthermore, when the melanin is water-soluble melanin, the solvent is water; when it is alcohol-soluble melanin, the solvent is ethanol; the mass ratio of melanin to solvent is 1:1-2.
[0020] Lubricating oil and hydraulic oil are oily pollutants that are often in contact with during the assembly and maintenance of engineering machinery. It is difficult to rinse them clean with water, and they are highly polluting. Standard samples of atmospheric test dust are found in GB13268, GB13269, and GB13270, which can simulate dust pollution in the air. Wetting agents can enhance the wetting of pollutants on the surface of the paint film, avoid the formation of a lotus leaf effect, and make it spread evenly on the surface of the paint film. Water-soluble or alcohol-soluble melanin mainly simulates the influence of pollutants on the color of the coating. Conventional carbon black is insoluble in water or solvents. After mixing with liquid, it exists in the form of solid particles. At the same time, simple stirring and dispersion is difficult to open the agglomerated carbon black. The particle size of its particle form is large, and it is difficult to penetrate into the pores on the surface of the coating, and the degree of pollution to the coating is not obvious. Therefore, the test body components selected by the present invention can simulate the actual environmental pollution of the engineering machinery coating in many aspects, which is representative.
[0021] The technical solution adopted by the present invention to solve the second technical problem is that the preparation method of the specimen includes the following steps: hydraulic oil, lubricating oil, wetting agent, atmospheric test dust standard sample, melanin, and solvent are added into a container in sequence, and stirred evenly at a speed of 500-700r / min to obtain a test specimen.
[0022] The technical solution adopted by the present invention to solve the third technical problem is a method for testing the anti-fouling performance of the coating of engineering machinery using the test body, comprising the following steps:
[0023] (a) preparing a test piece coating film, using a tinplate (the size of which is adapted to the size of the baking oven used, preferably 70×150 mm) to make a test piece, coating it with a coating for engineering machinery, the film thickness of which is controlled to be 40-60 μm, baking and drying, and forming a test piece coating film;
[0024] (b) Use a soft brush to apply the test specimen on the coating film of the test specimen in a crisscross pattern, with the amount of the test specimen applied being 2 g ± 0.1 g per test specimen, and curing for 24 h at a temperature of 23 ± 2° C. and a relative humidity of 50 ± 5%, to obtain a test specimen;
[0025] (c) Place the test specimen and the test body together in an artificial accelerated aging chamber, and take them out after testing according to the method specified in GB / T 1865-2009; artificial accelerated aging is xenon lamp aging;
[0026] (d) Prepare a 2% detergent solution according to the method specified in Section 6.2.1 of GB / T 9780-2013, wipe the specimen 20 times with a dust-free cloth soaked in the 2% detergent solution, rinse with tap water, and dry for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5%;
[0027] (e) Evaluate the anti-fouling performance of the coating according to visual staining, gloss loss and discoloration of the coating.
[0028] Furthermore, in step (a), the coating film is baked at a temperature of 70-85° C. (preferably 80° C.) and a baking time of 50-70 min (preferably 55-65 min, more preferably 60 min).
[0029] Furthermore, in step (c), the artificial accelerated aging is xenon lamp aging; the instrument is ATLAS CI-4400.
[0030] Furthermore, in step (c), the test method is to perform irradiation according to method 1 described in GB / T1865-2009, and perform a wetting cycle according to cycle A described in section 9.5 of GB / T1865-2009, i.e., wetting for 18 minutes and drying for 102 minutes, for a total test of 24 hours.
[0031] Further, in step (e), the visual staining, gloss loss and discoloration are in accordance with GB / T1766-
[0032] The stain resistance of coatings is evaluated according to the method specified in the 2008 "Rating Methods for Aging of Paint and Varnish Coatings".
[0033] There is usually a long time interval between the production and sales of construction machinery. It will be stored in the factory for a long time and requires regular maintenance during use. The pollution it faces is significantly different from the pollution faced by architectural paint coatings. For example, most of the pollution stains on construction machinery contain strongly adhesive substances such as lubricating oil and hydraulic oil. These pollutant stains are much more difficult to wash away than general dust. The pollutants faced by architectural paint coatings on the exterior walls of buildings usually do not contain such strongly adhesive substances and are mostly dust pollution, which can generally be removed by washing.
[0034] Furthermore, stain resistance tests in laboratory environments are generally difficult to simulate the sun and rain scenes in natural environmental conditions, and the natural exposure test time is too long and the test efficiency is extremely low. The test method of the present invention uses artificial accelerated aging to predict the long-term relevant performance of the coating system in a shorter test time. Through artificial lighting, water spraying, high temperature and other means, the scene of the natural environment in which the engineering machinery is operating is highly simulated to accelerate the test process and effectively improve the test efficiency.
[0035] The beneficial effects of the present invention are as follows: the stain resistance test specimen provided by the present invention is closer to the components contained in the environmental pollutants faced by engineering machinery during storage, maintenance and use; the provided test method, by adopting artificial accelerated aging, is closer to the actual climate environment of engineering machinery, and can truly and effectively reflect the stain resistance performance of the coating of engineering machinery, including gloss loss and discoloration; the test specimen material is easy to obtain, the specimen preparation method is simple to operate, and the preparation cost is low; the stain resistance performance of the coating of engineering machinery is tested by using the specimen of the present invention, and the method is simple, fast and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a visual effect diagram of the stain resistance test of the acrylic polyurethane coating test piece in Example 1;
[0037] Figure 2 This is a visual effect diagram of the stain resistance test of the acrylic polyurethane coating test piece in Example 2;
[0038] Figure 3 This is a visual effect diagram of the stain resistance test of the acrylic polyurethane coating test piece of comparative example 1;
[0039] Figure 4This is a visual effect diagram of the stain resistance test of the acrylic polyurethane coating test piece of comparative example 2;
[0040] Figure 5 This is a visual effect diagram of the stain resistance test of the coating on a crane in comparative example 3 after one year. DETAILED DESCRIPTION
[0041] The specific implementation of the present invention is further described below in conjunction with specific embodiments and drawings.
[0042] The raw materials used in the examples given below are: hydraulic oil is Changjiang Lubricant L-HM46, lubricating oil is GBW13986PAO lubricating oil density standard material, wetting agent is TEGO Twin 4100, coal fly ash is GBW08401 coal fly ash component analysis standard material, alcohol-soluble melanin is McLean melanin (alcohol-soluble), and ethanol is 95% industrial ethanol, all of which can be purchased from conventional channels. The polyurethane coating used in the test of the present invention is a commercially available solvent-based two-component high-grade acrylic polyurethane coating, which is used for the decoration and protection of a certain engineering crane; the fluorocarbon coating used in the test is a commercially available solvent-based polytrifluorochloroethylene coating, which is used in the field of engineering machinery.
[0043] Example 1
[0044] The specimen of the present embodiment is used for testing the stain resistance of the coating of engineering machinery, and is made by mixing oil substances and powder substances. The weight percentage of each raw material component is: 10% hydraulic oil, 10% lubricating oil, 5% wetting agent, 30% coal fly ash, 15% alcohol-soluble melanin, and 30% ethanol.
[0045] Specimen preparation method: hydraulic oil, lubricating oil, wetting agent, coal fly ash and alcohol-soluble melanin are added into a steel cup in sequence, and stirred evenly at a speed of 600 r / min to obtain a test specimen.
[0046] The test method includes the following steps:
[0047] (a) Preparation of test piece coating film: a 70×150 mm tinplate is used to prepare the test piece, and the test coating is applied to the surface of the tinplate with a film thickness of 40-60 μm, and baked at 80° C. for 60 min to form a test piece coating film;
[0048] (b) Use a soft brush to apply the prepared specimen on the coating surface of the specimen in a crisscross pattern. The amount of specimen applied is 2 g ± 0.1 g per piece. Curing is carried out at a temperature of 23 ± 2 ° C and a relative humidity of 50 ± 5% for 24 hours to obtain the test specimen;
[0049] (c) Place the coating test specimen and the specimen together in an ATLAS CI-4400 artificial accelerated aging chamber, irradiate according to Method 1 described in GB / T 1865-2009, perform a wetting cycle according to Cycle A described in Section 9.5 of GB / T 1865-2009, i.e., wetting for 18 minutes and drying for 102 minutes, and take out 24 hours after the test;
[0050] (d) Prepare a 2% detergent solution according to the method specified in Section 6.2.1 of GB / T 9780-2013, wipe the test sample 20 times with a dust-free cloth soaked in the 2% detergent solution, then rinse with tap water, and dry it for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5%;
[0051] (e) Evaluate the anti-staining performance of the coating according to the visual staining, gloss loss and discoloration described in GB / T 1766-2008.
[0052] Example 2
[0053] The specimen used for stain resistance test in this embodiment includes oil substances and powder substances, and the weight percentage of each raw material component is: hydraulic oil 30%, lubricating oil 30%, wetting agent 3%, coal fly ash 10%, alcohol-soluble melanin 9%, and ethanol 18%.
[0054] The preparation method and testing method of the stain resistance test specimen of this embodiment are the same as those of embodiment 1.
[0055] Comparative Example 1
[0056] According to the brushing method A specified in 5.4.1.2 of GB / T 9780-2013, fly ash was used as the pollution source to test the anti-fouling performance of the same paint film.
[0057] Comparative Example 2
[0058] According to the immersion method A specified in 5.5.1.2 of GB / T 9780-2013, a vaseline-carbon black mixture was used as the pollution source to test the anti-fouling performance of the same coating film.
[0059] Comparative Example 3
[0060] This comparative example uses the same solvent-based two-component high-grade acrylic polyurethane coating and is applied to the body surface of a large engineering crane. After being sold and used for one year, the coating appearance, gloss and color difference data are tracked and tested. The test results of the embodiment and the comparative example are shown in Table 1:
[0061] Table 1. Test results of examples and comparative examples
[0062]
[0063] The test specimen of Example 1 and the fly ash of Comparative Example 1 are used to simulate an environment with more dust pollution, and the test specimen of Example 2 and the vaseline carbon black mixture in Comparative Example 2 are used to simulate an environment with more oil pollution. From Examples 1 and 2 and Comparative Examples 1 and 2, the existing building coating stain resistance test specimens and test methods have no obvious pollution effect on polyurethane and fluorocarbon topcoats, and cannot distinguish the quality of the paint film stain resistance. The stain resistance test specimen and test method provided by the present invention can more effectively reflect the difference in the stain resistance performance of the coating. From the tracking data of Example 1, Example 2 and a certain crane one year later, the degree of gloss loss and discoloration is roughly the same, and the test specimen and test method provided by the present invention are closer to the actual situation.
[0064] The visual effects of the stain resistance test of the acrylic polyurethane coating films of Examples 1 and 2 of the present invention and Comparative Examples 1-3 are as follows: Figure 1-5 shown.
[0065] In summary, the stain resistance test specimen and test method provided by the present invention can quickly and effectively reflect the stain resistance performance of the engineering machinery coating.
[0066] The embodiments are only for those skilled in the art to more fully understand the present invention and understand the specific implementation methods of the present invention. They shall not be used to limit the scope of patent protection of the present invention. After reading this specification, those skilled in the art may make some modifications to the invention as needed, but as long as they are within the scope of the claims of the patent application of the present invention, they shall be protected by the patent law.
Claims
1. A specimen for testing the stain resistance of engineering machinery coatings, characterized in that: The invention is prepared by mixing the following raw material components in weight percentage: 10-30% of hydraulic oil, 10-30% of lubricating oil, 2-5% of wetting agent, 20-40% of standard sample of atmospheric test dust, 5-15% of melanin and 10-30% of solvent.
2. The test piece for testing the anti-fouling property of a coating on an engineering machinery according to claim 1, characterized in that: The hydraulic oil is L-HM anti-wear hydraulic oil (high pressure) or L-HM anti-wear hydraulic oil (ordinary) described in GB11118.
1.
3. A specimen for testing the stain resistance of engineering machinery coating according to claim 1 or 2, characterized in that: The medium lubricating oil is GBW13986 PAO lubricating oil density standard material.
4. A specimen for testing the stain resistance of engineering machinery coating according to claim 1 or 2, characterized in that: The wetting agent is TEGO 270 wetting agent or TEGO 4100 wetting agent.
5. A specimen for testing the stain resistance of engineering machinery coating according to claim 1 or 2, characterized in that: The standard sample of atmospheric test dust is loess dust and / or coal fly ash.
6. The test piece for testing the stain resistance of engineering machinery coating according to claim 1, characterized in that: The melanin is water-soluble melanin CAS 8005-03-6 or alcohol-soluble melanin CAS 8005-02-5.
7. A specimen for testing the stain resistance of a coating on an engineering machinery according to claim 1 or 2, characterized in that: The solvent is water or ethanol.
8. The test piece for testing the anti-fouling property of a coating on an engineering machinery according to claim 6, characterized in that: When the melanin is water-soluble melanin, the solvent is water; when the melanin is alcohol-soluble melanin, the solvent is ethanol; the mass ratio of melanin to solvent is 1:1-2.
9. A method for preparing a specimen for testing the stain resistance of a coating on an engineering machinery as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Hydraulic oil, lubricating oil, wetting agent, standard sample of atmospheric test dust, melanin and solvent are sequentially added into the container, and stirred evenly at a speed of 500-700 r / min to obtain a test specimen.
10. A method for testing the stain resistance of an engineering machinery coating using a test piece for testing the stain resistance of an engineering machinery coating as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (a) preparing a test piece coating, using a tinplate to make a test piece, coating the test piece with a coating for engineering machinery, the film thickness of which is controlled to be 40-60 μm, and baking and drying to form a test piece coating; the baking temperature is 70-85° C., and the baking time is 50-70 min; (b) using a soft brush to apply the test specimen on the coating film of the test specimen in a crisscross pattern, with the amount of the test specimen applied being 2 g ± 0.1 g per test specimen, and curing for 22-26 h at a temperature of 23 ± 2° C. and a relative humidity of 50 ± 5%, to obtain a test specimen; (c) The test specimen and the test body are placed in an artificial accelerated aging chamber, and taken out after testing according to the method specified in GB / T 1865-2009; the artificial accelerated aging is xenon lamp aging; the test is irradiated according to Method 1 of GB / T 1865-2009, and the wetting cycle is carried out according to Cycle A specified in Section 9.5 of GB / T 1865-2009, that is, wetting for 18 minutes and drying for 102 minutes, and the total test is 24 hours; (d) Prepare a 2% detergent solution according to the method specified in Section 6.2.1 of GB / T 9780-2013, wipe the specimen 20 times with a dust-free cloth soaked in the 2% detergent solution, rinse with tap water, and dry for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5%; (e) Evaluate the anti-staining performance of the coating according to the visual staining, gloss loss and discoloration of the coating; the visual staining, gloss loss and discoloration shall be evaluated according to the method specified in GB / T 1766-2008 "Rating method for aging of paints and varnishes".
Citation Information
Patent Citations
Rapid detection method for stain resistance of emulsion paint film
CN105445235A
Method used for rapid evaluation of stain resistance of coated plates, and special standard pollutant
CN105628624A
Anti-corrosive ship paint, and preparation method and application of paint
CN103627299A
Stain-resistant self-cleaning coating for engineering machinery and preparation method of stain-resistant self-cleaning coating
CN112341919A